Fiber Optic Splicing Testing Training for Vocational High School Students in Purwakarta - Endah Setyowati; Ahmad Fauzi; Galura Muhammad Suranegara; Vormes Gema Merdeka (Institut Teknologi Nasional, Bandung, 2023)
This activity aimed at improving the competence of SMK students in the fiber optic field that supports the development of broadband network technology in Indonesia. In addition, it was also to assist students in improving the basic competencies and core competencies of the Vocational High School curriculum for telecommunication access network engineering expertise. The activity was organized by the Telecommunication System Study Program at the Indonesian Education University Regional campus in Purwakarta, West Java in the Community Service (PkM) program. A total of 16 participants who were vocational students from several schools in Purwakarta Regency attended this activity. The method of implementing the workshop was the presentation of theory, practice, and evaluation by giving a questionnaire to the participants. The results of the participants' responses showed that they were satisfied with the implementation of this workshop (score 94.42 of 100).